Polyfuran-based chemical sensors: reactivity analysis via Fukui indexes and reactive molecular dynamics - Lascane, Leonardo Gois [UNESP]; Oliveira, Eliezer Fernando; Batagin-Neto, Augusto [UNESP] (Cambridge Univ Press, 2020)
In the present study we employ electronic structure calculations (based on Density Functional Theory -DFT approach) and Fully Atomistic Reactive Molecular Dynamics (FARMD) simulations (based on ReaxFF reactive force field) to evaluate the reactivity of branched polyfuran (PF) derivatives and identify promising systems for chemical sensing. Condensed-to-atoms Fukui indexes (CAFI) were employed to identify the most reactive sites on the oligomers structure. The chemical sensing abilities of the most promising systems were evaluated via FARMD simulations in the presence of distinct gaseous compounds. The results indicate the derivatives PF-CCH and PF-NO & x2082; (i.e. CCH and NO2 as side groups) as the most promising systems for chemical sensor applications, presenting higher reactivity on the most accessible sites. An interesting correspondence between DFT and MD results was also identified, suggesting the plausibility of using CAFI parameters for the identification of improved materials for chemical sensors.
Keywords: chemical substitution; electronic structure; polymer; optical properties